A CANONICAL CORRELATION APPROACH IN DETERMINING GROWTH & DEVELOPMENT AND SOCIAL INCLUSION LINKAGES - Şanlı, Sera (Bursa Teknik Üniversitesi, 2018)
In 2017 Inclusive Growth and Development Report published by World Economic Forum, Inclusive Growth and Development Key Performance Indicators have been based upon three dimensions as “Growth and Development (G&D)”, “Inclusion (INC)” and “Intergenerational Equity and Sustainability”. In this study, interrelations between G&D and INC dimensions have been tried to be revealed for totally 91 countries which take place in 2017 Report by carrying out Canonical Correlation Analysis. Standardized canonical coefficients have shown that ‘GDP per Capita’ variable has provided the largest contribution to G&D dimension and ‘Median Household Income’ variable has created the largest effect on INC set when the first canonical correlation is taken into consideration. Based on the communality coefficients, it can be said that ‘Employment’ variable may not represent a strong relationship with INC set. In addition, ‘Net Income Gini’ and ‘Wealth Gini’ variables have been detected not to be associated with G&D set.

In 2017 Inclusive Growth and Development Report published by World Economic Forum, Inclusive Growth and Development Key Performance Indicators have been based upon three dimensions as “Growth and Development (G&D)”, “Inclusion (INC)” and “Intergenerational Equity and Sustainability”. In this study, interrelations between G&D and INC dimensions have been tried to be revealed for totally 91 countries which take place in 2017 Report by carrying out Canonical Correlation Analysis. Standardized canonical coefficients have shown that ‘GDP per Capita’ variable has provided the largest contribution to G&D dimension and ‘Median Household Income’ variable has created the largest effect on INC set when the first canonical correlation is taken into consideration. Based on the communality coefficients, it can be said that ‘Employment’ variable may not represent a strong relationship with INC set. In addition, ‘Net Income Gini’ and ‘Wealth Gini’ variables have been detected not to be associated with G&D set.
A CANONICAL CORRELATION APPROACH IN DETERMINING GROWTH & DEVELOPMENT AND SOCIAL INCLUSION LINKAGES